Bickerstaff's encephalitis and Miller Fisher syndrome associated with voltage-gated potassium channel and novel anti-neuronal antibodies. - Tüzün, E; Kürtüncü, M; Lang, B; Içöz, S; Akman-Demir, G; Eraksoy, M; Vincent, A (2010)
BACKGROUND: GQ1b antibody (GQ1b-Ab) is detected in approximately two-thirds of sera of patients with Bickerstaffs encephalitis (BE). Whilst some of the remaining patients have antibodies to other gangliosides, many patients with BE are reported to be seronegative. METHODS AND RESULTS: Voltage-gated potassium channel antibody (VGKC-Ab) at high titer was detected during the diagnostic work-up of one patient with BE. Sera of an additional patient with BE and nine patients with Miller Fisher syndrome (MF) (all GQ1b-Ab positive) were investigated for VGKC-Ab and other anti-neuronal antibodies by radioimmunoprecipitation using 125I-dendrotoxin-VGKC and immunohistochemistry, respectively. Two patients with MF exhibited moderate titer VGKC-Abs. Regardless of positivity for VGKC or GQ1b antibodies, serum IgG of all patients with BE and MF reacted with the molecular layer and Purkinje cells of the cerebellum in a distinctive pattern. CONCLUSION: Voltage-gated potassium channel antibodies might be involved in some cases of BE or MF. The common staining pattern despite different antibody results suggests that there might be other, as yet unidentified, antibodies associated with BE and MF.